2014
DOI: 10.1021/ed4008765
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry Education: Ten Heuristics To Tame

Abstract: Students in our chemistry classes often generate shallow responses to our questions and problems. They fail to recognize relevant cues in making judgments and decisions about the properties of chemical substances and processes, and make hasty generalizations that frequently lead them astray. Results from research in the psychology of decision making can help us better understand how students approach chemistry tasks under conditions of limited knowledge, time, or motivation. In this contribution, I describe 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 62 publications
3
100
0
10
Order By: Relevance
“…The accompanying open‐ended responses were then examined through the lens of heuristics usage. Specific statements within the responses were assigned according to the 10 heuristics proposed by Talanquer . After preliminary examination of all open‐ended responses, only six of the ten heuristics, as well as non‐heuristic reasoning, were used to analyze this dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accompanying open‐ended responses were then examined through the lens of heuristics usage. Specific statements within the responses were assigned according to the 10 heuristics proposed by Talanquer . After preliminary examination of all open‐ended responses, only six of the ten heuristics, as well as non‐heuristic reasoning, were used to analyze this dataset.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Type 2 Reasoning requires slow, critical thinking to arrive at a solution. Mathematics, physics, and chemistry education studies have suggested that students' answers are often the result of Type 1 reasoning . The use of Type 1 Reasoning, or heuristics, can lead to a multitude of wrong answers and misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Theories involving these processes include such ideas as a "singularity principle," namely, that people tend to think of only one explanation at a time, (perhaps due to system 1 processes), and this can lead to ignoring alternative explanations [24]. In the last decade, science education researchers have also begun to explicitly note the importance of dual process theories when explaining student responses to tasks in science education settings [17,[25][26][27][28].…”
Section: A Theoretical Background and Contextmentioning
confidence: 99%
“…This phenomenon is analogous to the generalization heuristic where students recognize patterns but not the conditions in which the pattern is applicable. 17 It may be expected that the introduction of valence bond theory, in particular, orbital hybridization, may make the case, directly or indirectly, that electrons in molecules are not building within the same electron configuration. The results indicate this is not the case.…”
Section: ■ Results and Discussionmentioning
confidence: 99%